2017
DOI: 10.1038/bcj.2017.61
|View full text |Cite
|
Sign up to set email alerts
|

MYC is a positive regulator of choline metabolism and impedes mitophagy-dependent necroptosis in diffuse large B-cell lymphoma

Abstract: The activation of oncogenes can reprogram tumor cell metabolism. Here, in diffuse large B-cell lymphoma (DLBCL), serum metabolomic analysis revealed that oncogenic MYC could induce aberrant choline metabolism by transcriptionally activating the key enzyme phosphate cytidylyltransferase 1 choline-α (PCYT1A). In B-lymphoma cells, as a consequence of PCYT1A upregulation, MYC impeded lymphoma cells undergo a mitophagy-dependent necroptosis. In DLBCL patients, overexpression of PCYT1A was in parallel with an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Besides coordinating with HIF-1α the expression of several glucose transporters and glycolytic enzymes [213,214], c-Myc also modulates mitophagy by regulating choline metabolism. In B-lymphoma cells, c-Myc activates the transcription of the key enzyme phosphate cytidylyltransferase 1 choline-α (PCYT1A) and PCYT1A upregulation prevents lymphoma cells to undergo a mitophagy-dependent necroptosis [215].…”
Section: Mitophagy and Cancermentioning
confidence: 99%
“…Besides coordinating with HIF-1α the expression of several glucose transporters and glycolytic enzymes [213,214], c-Myc also modulates mitophagy by regulating choline metabolism. In B-lymphoma cells, c-Myc activates the transcription of the key enzyme phosphate cytidylyltransferase 1 choline-α (PCYT1A) and PCYT1A upregulation prevents lymphoma cells to undergo a mitophagy-dependent necroptosis [215].…”
Section: Mitophagy and Cancermentioning
confidence: 99%
“…Besides its widely documented apoptotic anticancer activity [ 163 ], berberine promoted necroptosis in ovarian cancer cells and in three patient-derived primary ovarian cancer cell lines (POCCLs) by activating RIP3 and MLKL [ 118 ] ( Table 2 ). Berberine triggered necroptosis also in diffuse large B-cell lymphoma (DLBCL) cancer cells, where the necroptotic mechanism has been deeply investigated [ 119 ] ( Table 2 ). In DLBCL cells, berberine promoted mitophagy-dependent necroptosis by inducing the formation of the RIP1/RIP3/MLKL necrosome complex and mRNA degradation of PCYT1A (phosphate cytidylyltransferase 1 alpha), thus reducing its expression in cancer cells [ 119 ] ( Table 2 ).…”
Section: Necroptosismentioning
confidence: 99%
“…PCYT1A is a rate-limiting enzyme for PC synthesized via the Kennedy pathway, which converts phosphocholine to CDP-choline 31 . Many studies have reported that the increase of PC synthesis is caused by the up-regulation of PCYT1A 11,19,31,32 . Furthermore, we examined the levels of the substrates for the PC biosynthesis in HepG2 and HepG2.2.15 cells and found that phosphocholine and CDP-choline increased in HepG2.2.15 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%